Everyday forms of collective action in Bangladesh: Learning from Fifteen Cases - Davis, Peter (International Food Policy Research Institute, 2009)
This paper examines fifteen cases of collective action in six villages in rural Bangladesh. Collective action was defined broadly and identified from significant episodes in previous life-history research in the same villages. The types of collective action identified were catalyzed by marriage; dowry and domestic violence; disputes over land; illness, injury and death in accidents; and theft and cheating. The role of development NGOs was less significant than would be expected considering their visibility in rural Bangladesh. The study suggests that ‘everyday forms’ (Scott 1985) of collective action often occur spontaneously and informally, with significant impact on peoples’ wellbeing, but with ambiguous outcomes for some poor people involved. This is a different picture that is usually understood in Bangladesh – due to the visibility of NGOs – particularly by outsiders. Local government elected chairs and members play a key role in collective action events, which often include local arbitration, or shalish, hearings. A deeper understanding of how collective disputes and struggles are commonly managed in everyday life should help us to hold a more realistic view of the empowerment potential of interventions aimed at fostering collective action in rural Bangladesh.